2017
DOI: 10.1039/c6ee03186b
|View full text |Cite
|
Sign up to set email alerts
|

Thienothiophene-based copolymers for high-performance solar cells, employing different orientations of the thiazole group as a π bridge

Abstract: The new strategy, employing thiazole as a π bridge into the backbone of quinoid polymers, enhanced the VOC and photovoltaic performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
89
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 110 publications
(95 citation statements)
references
References 43 publications
6
89
0
Order By: Relevance
“…As the Tz units increased, the HOMO energy level decreased. The results verified that the Cl atom that was substituted on the side chain and the Tz unit that was incorporated into the main chain could significantly reduce the HOMO energy level, which could favor high V OC in photovoltaic devices …”
Section: The Absorption Properties and Energy Values Of The Polymersmentioning
confidence: 57%
See 3 more Smart Citations
“…As the Tz units increased, the HOMO energy level decreased. The results verified that the Cl atom that was substituted on the side chain and the Tz unit that was incorporated into the main chain could significantly reduce the HOMO energy level, which could favor high V OC in photovoltaic devices …”
Section: The Absorption Properties and Energy Values Of The Polymersmentioning
confidence: 57%
“…With the introduction of a thiazole (Tz) moiety, the HOMO energy level significantly decreased, and the backbone planarity increased. Accordingly, the V OC gradually increased from 0.68 V for polymer PBDTTT‐E‐T without thiazole to 0.78 V for polymer PBTzT‐4 with one thiazole unit and 0.83 V for polymer PTBTz‐2 with two units . In addition, the position of the halogen atom also has a significant impact on intermolecular self‐assembly of the conjugated polymers .…”
Section: The Absorption Properties and Energy Values Of The Polymersmentioning
confidence: 99%
See 2 more Smart Citations
“…To facilitate the calculation, side alkyl chains were simplify to methyl groups. [41] For the electron distribution, it can be observed that the HOMO surface of the polymers delocalize in both TBD and accept units and the LUMO surface of the polymers mainly localize in the acceptor units. The moderate twisting geometry was beneficial to improve the solubility and inhibit strong aggregation of the corresponding polymers.…”
Section: Resultsmentioning
confidence: 98%